Exploring the sustainable teaching and learning in Nigerian schools with focus on emergency remote education - Olatunbosun Emmanuel Ogunseemi; Oladele Dennis Omodara; Mercy Adesola Daramola (International Journal of Evaluation and Research in Education (IJERE), 2026)
The global pandemic was a great challenge to delivering education in Nigerian schools. This undoubtedly came with a sudden shift to remote learning when teachers and students alike had to adapt to emergency remote education. Although, the prediction of international organizations on the effect of school closure during pandemic perhaps stimulated the emergent of remote teaching and learning (RTL) globally and particularly, in Nigeria. However, it was observed that the innovation and reformation has provided opportunities for transformation through borderless learning which is actually apt for situations like the COVID-19 pandemic. This article therefore, utilized naturalistic observation strategy to explore the impact of this shift on sustainable teaching and learning in schools in Ekiti State, Nigeria. It discusses the concept of emergency remote education as it relates to Nigerian education system. More importantly, it exposed the technology usage in classroom practices in Ekiti State, Nigeria vis a vis, the experiences of teachers and students in emergency remote education, highlighting the platforms employed, successes recorded and challenges encountered in the process. It was concluded that stake holders in Nigerian education system have been navigating unexplored territory to ensure continuous learning. Recommendations were made on how to improve the practice of remote education in Nigeria.